Optimal Water-Nutrient Norms and Irrigation Regimes of Fine-Fiber St-1651 Cotton Variety in Light Gray Soils of Surkhandarya Region - Boynazarov Odil Sharofovich; Ashurov Shavkat Shodmonovich; Bobirova Madina Bobir qizi (Zien Journals, 2021)
The article examines the fertilizer thickness irrigation system of fine-grained cotton variety ST-1651 in light gray soils of Surkhandarya region.
Keywords: Light gray soil; fine-grained ST-1651 cotton variety; fertilization standards; seedling thickness